The macroeconomic factors that influence non-performing loan on banking and financial institution in Malaysia / Jalis Md Zainol - Md Zainol, Jalis (Faculty of Business and Management, 2018)
This paper studies empirically the movement of non-performing loan (NPL) on banking and financial institutions in Malaysia. The period of the research taken was in range of 10 years and use of quarterly data ranged from Q12006 to Q42015. The study will use Auto-Regressive Distributed Lag (ARDL) method to see the significant and relationships between dependent and independent variables in long run elasticity. The dependent variable of the study is the NPL. The independent variables were selected and identified namely as Gross Domestic Product (GDP), Base Lending Rate (BLR), Inflation (INF) and Household Income Distribution (HPI). The level of NPL will be affected by the macroeconomic condition in Malaysia. According to the overall results in this study it indicates the most of independent variables are given an impact to the NPL at Malaysia. However, the result of significant is conversely with previous study. The relationship implies that GDP are significant negatively towards NPL, meanwhile BLR and ID are significant positive toward NPL. But INF is insignificant negative relationship towards NPL. The result of this research will be very useful for other researchers and banking institution that aware about the movement of NPL at Malaysia.